2018
DOI: 10.1155/2018/4093285
|View full text |Cite
|
Sign up to set email alerts
|

CYP1A1 Relieves Lipopolysaccharide-Induced Inflammatory Responses in Bovine Mammary Epithelial Cells

Abstract: The expression of cytochrome P4501A1 (CYP1A1) enzyme is changed in various organs during the host response to inflammation or infection, leading to alterations in the metabolism of endogenous and exogenous compounds. Results of this study showed that CYP1A1 expression was significantly downregulated in the mammary tissue of bovine with mastitis, in inflammatory epithelial cells (INEs) extracted from the tissue, and in lipopolysaccharide- (LPS-) induced INEs compared with their corresponding counterparts. Overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 37 publications
(45 reference statements)
2
13
0
Order By: Relevance
“…With respect to molecular changes, we observed that while the expression of the majority of mRNAs increased in the tumor cells upon MΦ infiltration, CYP1A1 expression appeared to be inhibited. This corroborates previous findings that inflammatory conditions, induced by LPS or found during mastitis, suppress CYP1A1 expression in mammary epithelial cells [13]. In contrast to epithelial cells, enhanced CYP1A1 expression in response to LPS was shown in human dendritic cells [24].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…With respect to molecular changes, we observed that while the expression of the majority of mRNAs increased in the tumor cells upon MΦ infiltration, CYP1A1 expression appeared to be inhibited. This corroborates previous findings that inflammatory conditions, induced by LPS or found during mastitis, suppress CYP1A1 expression in mammary epithelial cells [13]. In contrast to epithelial cells, enhanced CYP1A1 expression in response to LPS was shown in human dendritic cells [24].…”
Section: Discussionsupporting
confidence: 91%
“…In line, polymorphisms associated with higher CYP1A1 activity have been associated with elevated breast cancer risk [10, 11]. Interestingly, CYP1A1 expression commonly appears to be repressed by inflammatory mediators [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…S5B ). Moreover, VIPR1 , CYP1A1 and PPP1R14A are reported to be strongly associated with the modulation of inflammatory and/or innate immune responses as their downregulation results in the elevation of immune responses ( Abad et al., 2016 ; Blackham et al., 2010 ; Delgado et al., 2001 ; Fang et al., 2016 ; Paton and Renton, 1998 ; Yin et al., 2017 ; Zhang et al., 2018 ) during microbial infections, autoimmunity and dendritic cell differentiation respectively. Altogether, our result concludes that these metabolic pathways-related genes or cellular factors contributes in elevation of RNA virus infection and causing lung disease severity in presence of airborne ambient PM.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, no study in cattle has established the relative contribution of differing CYP450 to the overall oxylipid pool. Due to this, CYP450 that metabolize PUFA chosen for this study were selected based on their significant contribution to the oxylipid pool in other species, such as CYP2C19, CYP2E1, CY-P3A4, CYP4A11, and CYP4F2, or previous research in cattle that has explored the activity of a specific CYP450, such as CYP1A1 or CYP2J2 (Lasker et al, 2000;Yang et al, 2001;Fer et al, 2008;Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%